Grounds of goodness - Fix, J (Journal of Philosophy, 2023)
What explains why we are subjects for whom objects can have value, and what explains which objects have value for us? Axiologicians say that the value of humanity is the answer. I argue that our value, no matter what it is like, cannot perform this task. We are animals among others. An explanation of the value of objects for us must fit into an explanation of the value of objects for animals generally. Different objects have value for different animals. Those differences depend on differences in animal natures and, in particular, on the diverse characteristic capacities of different animals. Once we invoke animal natures, there is nothing for the value of animality, including the value of humanity, to explain.